2006
DOI: 10.1021/bi0600852
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Kinetic Characterization of the Michaelis Charge Transfer Complex in Monomeric Sarcosine Oxidase

Abstract: Monomeric sarcosine oxidase is a flavoenzyme that catalyzes the oxidation of the methyl group in sarcosine (N-methylglycine). Rapid reaction kinetic studies under anaerobic conditions at pH 8.0 show that the enzyme forms a charge transfer Michaelis complex with sarcosine (E-FAD(ox).sarcosine) that exhibits an intense long-wavelength absorption band (lambda(max) = 516 nm, epsilon(516) = 4800 M(-)(1) cm(-)(1)). Since charge transfer interaction with sarcosine as donor is possible only with the anionic form of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
54
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 24 publications
7
54
1
Order By: Relevance
“…This feature suggested that the reductive half-reaction with Lys265Met is initiated by the formation of an enzyme•substrate charge transfer complex, similar to that observed with wild-type MSOX (12). Consistent with this hypothesis, initial spectra observed after mixing Lys265Met with a wide range of sarcosine concentrations (1 to 140 mM) are isosbestic (Figure 5A) and show the progressive formation of a charge transfer band that exhibits a maximum at 495 nm, as estimated by the position of the peak in the corresponding difference spectrum (Figure 6A).…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…This feature suggested that the reductive half-reaction with Lys265Met is initiated by the formation of an enzyme•substrate charge transfer complex, similar to that observed with wild-type MSOX (12). Consistent with this hypothesis, initial spectra observed after mixing Lys265Met with a wide range of sarcosine concentrations (1 to 140 mM) are isosbestic (Figure 5A) and show the progressive formation of a charge transfer band that exhibits a maximum at 495 nm, as estimated by the position of the peak in the corresponding difference spectrum (Figure 6A).…”
Section: Resultssupporting
confidence: 64%
“…An isosbestic spectral course is observed for the anaerobic reduction of wild-type MSOX over a wide range of sarcosine concentrations (1 to 80 mM) in reactions that exhibit a monophasic exponential loss of oxidized enzyme absorbance (12). Apparently similar features are observed for the reductive half-reactions with Lys265Met or Lys265Arg but only at sarcosine concentrations below 25 or 10 mM, respectively (data not shown, see Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations